Translocation of elements and fractionation of Mg, Cu, Zn, and Cd stable isotopes in a penny bun mushroom (Boletus edulis) from western Czech Republic - Andronikov, Alexandre V; Andronikova, Irina E; Martinkova, Eva; Sebek, Ondrej; Stepanova, Marketa (Environmental science and pollution research international, 2023)
Boletus edulis mushroom behaved as an accumulating biosystem with respect to Ag, Rb, Zn, and K. The mushroom was not an efficient accumulator of toxic As, Pb, and Cr, but Se and Cd displayed much higher concentrations in the mushroom than in the substrate samples. Other elements were bioexclusive. Different elements had different within-mushroom mobilities. The highest mobilities were displayed by Zn and Ag, and the lowest by Ti. The mushroom's fruiting body preferentially took up lighter Mg, Cu, and Cd isotopes (Δ26MgFB-soil = -0.75‰; Δ65CuFB-soil = -0.96‰; Δ114CdFB-soil = -0.63‰), and the heavier 66Zn isotope (Δ66ZnFB-soil = 0.92‰). Positive within-mushroom Zn isotope fractionation resulted in accumulation of the heavier 66Zn (Δ66Zncap-stipe = 0.12‰) in the mushroom's upper parts. Cadmium displayed virtually no within-mushroom isotope fractionation. Different parts of the fruiting body fractionated Mg and Cu isotopes differently. The middle part of the stipe (3-6 cm) was strongly depleted in the heavier 26 Mg with respect to the 0-3 cm (Δ26Mgstipe(3-6)-stipe(0-3) = -0.73‰) and 6-9 cm (Δ26Mgstipe(6-9)-stipe(3-6) = 0.28‰) sections. The same stipe part was strongly enriched in the heavier 65Cu with respect to the 0-3 cm (Δ65Custipe(3-6)-stipe(0-3) = 0.63‰) and 6-9 cm (Δ65Custipe(6-9)-stipe(3-6) = -0.42‰) sections. An overall tendency for the upper mushroom's parts to accumulate heavier isotopes was noted for Mg (Δ26Mgcap-stipe = 0.20‰), Zn (Δ66Zncap-stipe = 0.12‰), and Cd (Δ114Cdcap-stipe = 0.04‰), whereas Cu showed the opposite trend (Δ65Cucap-stipe = -0.08‰).
Keywords: Trace elements; Agaricales; Soil Pollutants; látky znečišťující půdu; Isotopes; půda; Zinc; Non-traditional stable isotopes; zinek; Cadmium; izotopy; Czech Republic; kadmium; Fruiting body; Mushroom; Soil; Česká republika; Basidiomycota; Translocation